MIRRORING OF CONSUMPTIVE BEHAVIOR IN THE SPEECH ACTS OF THE MAIN CHARACTER IN THE FILM CONFESSION OF A SHOPAHOLIC (2009) - Amira Nadhira; Henny Suharyati; Dyah Kristyowati (Universitas Pakuan, 2022)
This study aims to (1) identify the forms and types of illocutionary and perlocutionary effects that reflect consumptive behavior towards the main character in the speech in the film Confession of a Shopaholic, (2) analyze the meaning of speech acts contained in the speech of the main character of the film and social issues, namely consumptive behavior, (3) Identify issues of consumptive behavior contained in the corpus and relate to consumptive culture in America in the middle class. The method used in the study is qualitative. The data is taken from the main character’s utterances, reflecting consumptive behavior collected using the listening method and the note method. The results showed illocutionary speech acts with representative, commissive, expressive, and directive types. Perlocutionary speech acts with verbal and non-verbal types. The words of the main character words the issue of consumptive behavior such as owning branded goods, and buying goods whose benefits are not clear only attract the attention of others, and become trendsetters.Keywords: illocutionary speech acts; perlocutionary speech acts; consumptive behaviour.